Regression-Based Norms for the Brief Visuospatial Memory Test-Revised in Italian population and application in MS patients. (23rd December 2016) - Argento, Ornella; Smerbeck, Audrey; Pisani, Valerio; Magistrale, Giuseppe; Incerti, Chiara C.; Caltagirone, Carlo; Benedict, Ralph H. B.; Nocentini, Ugo
Abstract: Objective: The Brief Visuospatial Memory Test-Revised (BVMT-R) is one of the most widely used tests for the assessment of learning and memory in the visual/spatial domain. The aim of this study was to use multiple regression to derive normative data for the use of BVMT-R in an Italian population.Method: We employed a regression-based norms procedure to maximally utilize a relatively small sample while controlling for a variety of demographic factors in addition to age. Additionally, we used these norms to compare the performance of Italian healthy controls with patients diagnosed with multiple sclerosis (MS), thereby providing evidence of the method's validity.Results: A total of 200 healthy volunteers and 70 MS patients participated in this study and completed the BVMT-R according to the published procedures. Regression-based norms were generated for the Italian sample and are presented herein.Conclusions: Using these norms, the performance of the MS patients was found to be significantly worse than that of the controls.